HUBUNGAN ANTARA POLA MAKAN DAN TINGKAT KONSENTRASI DALAM BELAJAR PADA MAHASISWA: (STUDI KASUS : MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA) - Ridwan Prasetyo; Frans Destri Bintang S; Raka Rossian Saputra; Yossie Saputra; Muhammad Thoriq; Fajar Muhammad (CV. ADIBA ASIHA AMIRA, 2024)
The purpose of this study is to find out whether or not there is a significant relationship with diet and concentration levels in learning in students of Bhayangkara University Jakarta Raya. The data analysis methods used in this study are the Kormogolov-Smirnov Normality Test and the Correlation Test. The discussion of this study is to test 2 variables with a normality test to find out whether the data tested is normally distributed or not, and a correlation test to find out whether there is a significant relationship between diet and concentration level in learning in students. The conclusion of this study is that there is a significant relationship between 2 variables, namely diet and concentration level.